Analisis Risiko Pembiayaan Mudharabah Dan Musyarakah Pada PT. Bank Sumut Unit Usaha Syariah - Nuridawati Cibro; Sri Sudiarti; Muhammad Syahbudi (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The allocation of bank funds is dominated by the distribution of funds in the form of financing, both Mudharabah and Musyarakah. In every financing, there must be a risk arising from the failure of the party to fulfill its obligations. The risk of Mudharabah and Musyarakah financing is potentially high because it relies on very high trust as a moral guarantee so that this is the background of this research. This study aims to determine what are the risks arising from mudharabah and musyarakah financing at PT Bank Sumut UUS. This research uses a descriptive qualitative approach with interviews, documentation and observation as data collection techniques. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusion drawing and verification. The results showed that the risks arising from mudharabah financing are financial risk (default), investment, legal, compliance, and fiduciary risk, but the risk of default is the most vulnerable where mudharib cannot fulfill his obligations to shahibul maal. Risks that arise due to musyarakah financing of PT Bank Sumut UUS include business risk (risk of financed business), shirinking risk (risk of reduced financing value) and character risk.